Sleep duration, sleep loss and depression - Turunen, Sirkku (My University, 2020)
The aim of this study was to examine if the onset of short sleep and sleep loss were associated with increased risk of depression by using Health and Social Support (HeSSup) data of working aged Finns. Previous studies on sleep duration and depression suggest that short sleep is an indicator of later depression, but there are some methodological limitations. Experimental studies on the effects of sleep loss on mood suggest that there is a link between sleep loss and depression. To my knowledge, no previous epidemiological studies on sleep loss and depression exists. HeSSup study comprises of population based survey data from three measuring points in 1998, 2003 and 2012. In the current study, the observational data were treated as pseudo-trial, mimicking a clinical trial regarding inclusion and exclusion criteria. Participants were included if they had average sleep duration (study 1) or no sleep loss (study 2) in the first measurement and no depression in the first or second measurement. In the sleep duration study (study 1), it was examined whether possible change in sleep duration from average (1998) to short (2003) predicted the onset of depression (2012), compared with persistent average sleep duration. In the sleep loss study (study 2), possible change from not experiencing sleep loss (1998) to experiencing sleep loss of 1 hour or 1.5 hours or more compared with persistently not experiencing sleep loss (2003) was analysed. The data were analysed using logistic regression analysis. In study 1, after full adjustment for demographic and health related covariates in 1998, change in sleep duration was associated with increased risk of developing depression by 43% [odds ratio 1.43, 95% confidence interval 1.02–2.00]. In study 2, sleep loss of 1.5 hours or more increased the risk of depression by 65% [odds ratio 1.65, 95% confidence interval 1.04–2.64]. Sleep loss of 1 hour was not associated with incident depression. These studies suggest that change in sleep duration from average to short and change from not experiencing sleep loss to experiencing 1.5 hours of sleep loss or more increase the risk of depression.
Keywords: Sleep duration, sleep loss, depression, observational data, longitudinal study, pseudo-trial